miR-181a-2-3p Stimulates Gastric Cancer Progression via Targeting MYLK - Li, Jianjie; Xu, Xiaoyue; Liu, Chunhui; Xi, Xiaoxue; Wang, Yang; Wu, Xiaotang; Li, Hua (Frontiers in Bioengineering and Biotechnology, 2021)
Background: The abnormal expression of miRNAs facilitates tumorigenesis and development. miR-181a-2-3p is up-regulated in various cancers, yet its mechanism in gastric cancer (GC) remains elusive. Objective: To understand mechanism of miR-181a-2-3p stimulating GC cell progression via targeting Myosin Light Chain Kinase (MYLK) expression. Methods: Downstream genes of miRNA of interest were predicted in TargetScan and miRTarBase. qRT-PCR and western blot were applied to assess miR-181a-2-3p and MYLK expression in GC cells and normal cells. Dual-luciferase and RIP assays were completed to assess binding of miR-181a-2-3p and MYLK. CCK-8 assay was conducted for detecting viability of AGS and SNU-1 cells, while Transwell tested migratory and invasive abilities of cells. Nude mouse transplantation tumor experiment was performed to assay tumor growth in vivo. Results: miR-181a-2-3p was notably increased in human GC cell lines, while MYLK was remarkably down-regulated. RIP and dual-luciferase assay disclosed that miR-181a-2-3p targeted MYLK and repressed MYLK. Forced miR-181a-2-3p expression fostered GC cell proliferation, invasion, migration, and fostered tumor growth in vivo. Promoting effect of miR-181a-2-3p on GC cells was reversed when miR-181a-2-3p and MYLK were simultaneously overexpressed. Conclusion: miR-181a-2-3p facilitated GC cell progression by targeting MYLK, and it may be a pivotal prognostic biomarker in investigating molecular mechanism of GC. Keywords: miR-181a-2-3p; MYLK; gastric cancer; proliferation; migration